Artificial intelligence and firm-level productivity - Dirk Czarnitzki; Gastón P. Fernández; Christian Rammer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Artificial Intelligence (AI) is often regarded as the next general-purpose technology with a rapid, penetrating, and far-reaching use over a broad number of industrial sectors. A main feature of new general-purpose technology is to enable new ways of production that may increase productivity. So far, however, only very few studies investigated likely productivity effects of AI at the firm-level; presumably because of lacking data. We exploit unique survey data on firms' adoption of AI technology and estimate its productivity effects with a sample of German firms. We employ both a cross-sectional dataset and a panel database. To address the potential endogeneity of AI adoption, we also implement an IV approach. We find positive and significant effects of the use of AI on firm productivity. This finding holds for different measures of AI usage, i.e., an indicator variable of AI adoption, and the intensity with which firms use AI methods in their business processes.
Keywords: O14; O31; O33; L25; M15; 330; Artificial Intelligence; Productivity; CIS data